ANALISIS INPUT DAN LINGKUNGAN IBU MENYUSUI TERHADAP PROGRAM PEMBERIAN ASI EKSKLUSIF (Studi Kasus Puskesmas Pandanaran Kota Semarang) - Made Weni Juliani Wismantari; Chriswardani Suryawati; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The exclusive breastfeeding program organized by primary health center is an assurance that children get exclusive breastfeeding. Pandanaran Primary Health Center is one of the health centers that has lowest exclusive breasfeeding coverage and the many mothers who have not been able to optimize their exclusive breastfeeding. The research objective is to describing the input and the mother's environment. The research method uses qualitative research with a descriptive analytic approach. This study interviewed 15 informants. The results of the study show that the input elements, resources were good, the availability of personel, money, and the availability of SOP. Facilities and infrastructure are available, but lactation room conditions are less functioning. In the environmental element, socio-cultural influence and employment status are things that hinder exclusive breastfeeding, even though the mother has the support of her husband, family and community. The advice that can be given to the Pandanaran Health Center, support in improving and developing competencies of health workers and preparing a better lactation room.